Environmental Analysis Of The Aedes Aegypti Mosquito As Dhf Vector In The Enrekang District - Dicky Alamsyah; Syamsuar Manyullei; Hasanuddin Ishak (Politeknik Kesehatan Kemenkes Mamuju, 2024)
Dengue Hemorrhagic Fever is a major health problem in Indonesia. The existence of the Aedes Aegypti mosquito is the main vector that causes Dengue Hemorrhagic Fever (RI Ministry of Health, 2020). The physical environment of the Aedes Aegypti mosquito greatly influences the ecology and development of the Aedes Aegypti mosquito, which is the main factor causing Dengue Hemorrhagic Fever (Listiono et al, 2020). The incidence of Dengue Fever in the people of Enrekang Regency is influenced by the physical environment of the Aedes Aegypti mosquito. Data on the physical environment of the Aedes Aegypti mosquito in the Enrekang Regency area is inadequate. In the Enrekang district area, there were 166 cases of dengue fever in 2019, in 2020 there was an increase of 209 cases and there was a decrease again in 2021 with 64 cases. Cases of Dengue Hemorrhagic Fever sufferers in Enrekang district are among the 10 highest diseases. The aim of the research is to determine the relationship between the physical environment (temperature, pH, humidity and residential density) of the Aedes Aegypti mosquito and the incidence of Dengue Hemorrhagic Fever in Enrekang district. The method in this research is analytical observational using a Case Control study approach. Analytical observational research is research that tries to identify how health phenomena occur. Sampling was carried out using the total sampling method. Data was obtained directly from the Enrekang District health office. The research results showed that there was a significant relationship between room temperature, water pH and room humidity with the incidence of Dengue Hemorrhagic Fever in Enrekang district with respective p-values of (0.007, 0.001 and 0.000). The results of the research show that the physical environment of the Aedes Aegypti mosquito is a risk factor for the occurrence of Dengue Fever in Enrekang district.